Pengujian Potensi Jus Tomat (Lycopersicum esculentum) Sebagai Terapi Herbal Pada Tikus Rattus norvegicus Hiperkolesterolemik - Dina Aribah; Alif Rofiqotun Nurul Alimah; Anindya Nirmala Permata; Betty Lukiati (Biogenesis: Jurnal Ilmiah Biologi, 2016)
Hypercholesterolemia defines as the increasing of cholesterol serum that more than the normal limit. WHO (2011) on 2008 at Indonesian said that hypercholesterolemia prevalence of woman approach about 37,2% and for man about 32,8%. Tomato contain lycopene is one powerful antioxidant and can manage cholesterol metabolism with blocked the HMG-KoA enzyme reductase (enzyme for cholesterol synthesis in hepar). This study aims to determine the effect of tomato juice on the cholesterol levels in the blood of hypercholesterolemic rats and to find the effective dosis of tomato juice to decrease the cholesterol of hypercholesterolemic rats. The object of research covering 20 wistar rats (Rattus norvegicus) male 2-3 months old with 50-150g weight. The rats were divided into five groups and four replications: normal (K-), high-fat diet (K+), high-fat diet+tomato juice 200mg/100gBB (P1), high-fat diet+tomato juice 400mg/100gBB (P2), high-fat diet+tomato juice 800mg/100gBB (P3). Tomato juice was given orally for one month every day. At the end of the treatment of rats was dissected to take blood from the heart. Data were analyzed statistically with one-way ANAVA with α=0,05. The results showed that the tomato juice affects on the cholesterol levels of blood serum of hypercholesterolemic rats and the effective dose of tomato juice used in this study was 800mg/100gBB.